가구구조 변화가 서비스 수요에 미치는 효과 분석 - 황수경 (12096, 2011)
This paper investigates the effects of changes in household structure on service demand. The structure of households in Korea has been quickly changed due to low birth rate and population aging as well as increasing women’s participation in the workforce